Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1002/syn.22192
|View full text |Cite
|
Sign up to set email alerts
|

Traffic noise exposure, cognitive decline, and amyloid‐beta pathology in an AD mouse model

Abstract: Concerns are growing that exposure to environmental pollutants, such as traffic noise, might cause cognitive impairments and predispose individuals toward the development of Alzheimer's disease (AD) dementia. In this study in a knock‐in mouse model of AD, we investigated how chronic traffic noise exposure (CTNE) impacts cognitive performance and amyloid‐beta (Aβ) pathology. A group of APPNL‐G‐F/NL‐G‐F mice was exposed to CTNE (70 dBA, 8 hr/day for 1 month) and compared with nonexposed counterparts. Following C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…Impaired learning and memory along with deterioration in motor skills and elevated anxiety are common symptoms of AD in humans. A series of studies in our lab have shown the similar deficits in APP mice (Jafari, et al, 2017(Jafari, et al, , 2018(Jafari, et al, , 2019Mehla et al, 2019;Karem et al, 2021). In addition, the declined cognitive and motor skills are associated with the formation of Aβ plaques and with age as the formation of Aβ plaques increases with age in these APP mice (Jafari et al, 2018;Mehla, et al, 2019).…”
Section: Early Ts Improves the Ad-like Symptoms In Adult Offspring At...mentioning
confidence: 78%
See 1 more Smart Citation
“…Impaired learning and memory along with deterioration in motor skills and elevated anxiety are common symptoms of AD in humans. A series of studies in our lab have shown the similar deficits in APP mice (Jafari, et al, 2017(Jafari, et al, , 2018(Jafari, et al, , 2019Mehla et al, 2019;Karem et al, 2021). In addition, the declined cognitive and motor skills are associated with the formation of Aβ plaques and with age as the formation of Aβ plaques increases with age in these APP mice (Jafari et al, 2018;Mehla, et al, 2019).…”
Section: Early Ts Improves the Ad-like Symptoms In Adult Offspring At...mentioning
confidence: 78%
“…There is plenty of evidence from clinical research on humans showing that people living in major cities (Astell-Burt & Feng, 2018) and closer proximity to heavy traffic noise (Chen et al, 2019) have higher chance of being diagnosed with AD/dementia along with other cognitive impairment disorders (Tzivian et al, 2016). Previous research in our lab has demonstrated the adverse effects of auditory stress on the brain and behaviour in second generation of mouse model of AD (Jafari et al, 2017;Mehla et al, 2019;Karem et al, 2021). In this study, we aimed to explore the role of early tactile stimulation (TS) in mitigating the adverse effects of gestational auditory stress, as well as AD-like symptoms in adult APP offspring.…”
Section: Introductionmentioning
confidence: 99%
“…In the critical period of hearing, continuous white noise exposure can change the bidirectional thalamic cortical plasticity of rat auditory cortex (Speechley et al, 2007). Continuous noise exposure may induce the aggregation of Aβ and cognitive impairment in mice (Karem et al, 2021). Moderate noise exposure during the early development of mice increases the density of GABA and somatostatin (SOM) cells in the primary auditory cortex (Au1) and the anterior auditory field (AAF), but decreases the density of perineural network cells in Au1.…”
Section: Introductionmentioning
confidence: 99%